PERBANDINGAN HASIL ANALISIS PERKERASAN KAKU DARI PEDOMAN BINA MARGA TAHUN 2003 DAN BINA MARGA TAHUN 2013 - M.Syaiful Afif; Doni Ramadhan; Djoko Purwanto; Bagus Hario (Jurnal Karya Teknik Sipil, 2016)
The attempt to provide toll road in Java has been developed rapidly. In the Solo-Semarang route, the construction has reached packet 3 Bawen-Salatiga. An issue in packet 3 appeared in packet 3.1 between Sta 22+900 - Sta 23+500 because it is located in a clayshale deposit area (Kerek Formation). Based on the N-SPT data obtained from drill test for excavation structure, clayshale was not found in the layer. From the soil description and geological review, the layer was dominated by tuff breccia with andesite fragment. In the embankment of STA 22+975, CPT and geoelectric tests were taken and the result from geoelectric showed the presence of claystone which is the main material of Kerek Formation. Therefore, the embankment is the weakest zone by ground movement. FEM analysis results were compared using LEM method by Plaxis 8.2 and Slope/W 2007. FoS acquired from the two methods showed insignificant changes. The static load calculation result proved that the FoS of excavation and embankment structure was bigger than the minimum standard required by USACE (FoS>1.30). FoS of embankment with two configurations had a considerable value. The application of quake load in accordance with 2010 earthquake zone map with 0.44 g acceleration revealed a variety of FoS. In terms of the security over the excavation, the FoS was bigger than the minimum requirement, which is >1.10.